Defense Surveillance System at the Interface: Response of Rice Towards Rhizoctonia solani During Sheath Blight Infection - Udita Acharya; Troyee Das; Zhumur Ghosh; Anupama Ghosh (Molecular Plant-Microbe Interactions, 2022)
Sheath blight of rice caused by necrotrophic plant pathogen Rhizoctonia solani is one of the most common fungal diseases of rice leading to significant yield loss. Among the defense responses exhibited by the host plants towards fungal infections, those functional within the apoplast contribute significantly. Here, we have studied apoplastic defense response of rice towards R. solani during sheath blight infection. The transcriptome of R. solani–infected rice plants was compared with that of uninfected rice, to identify the set of defense genes that undergo differential expression and code for proteins with a predicted N-terminal signal peptide. Significant changes in the stress-responsive, molecular signal perception, protein modification, and metabolic process pathways represented by a group of differentially expressed genes were observed. Our data also revealed two secreted protease inhibitors from rice that exhibit increased expression during R. solani infection and induce disease resistance when expressed in Nicotiana benthamiana. [Graphic: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.